La expresión plástica y su incidencia en el desarrollo psicomotriz de los niños y niñas de primer año de educación básica de la escuela José Miguel Burneo Burneo del barrio Obrapia de la ciudad de Loja. Periodo 2014 - Calero Torres, Jenny Cecibel (2015)
The object of the research was to study PLASTIC EXPRESSION AND ITS IMPACT ON DEVELOPMENT PSYCHOMOTOR CHILDREN FIRST YEAR OF BASIC EDUCATION SCHOOL JOSÉ MIGUEL BURNEO BURNEO. This thesis tries to shape our acquired knowledge about what investigated which will serve to help improve the education of children today who are the reason for the inspiration and the future of our country, artistic expression is the starting point for help in learning psychomotor children. For the present study the overall objective was formulated: Conduct a study on strategies in Plastic Expression employing teachers to enhance the psychomotor development of children. He also raised specifically look for three aspects: first Contributing to research on the visual expression of the first year of basic education and thus determine the level of psychomotor second development, Meet the training and knowledge of teachers regarding the analysis of artistic expression and its use as a tool for the development of psychomotor skills and third Knowing whether the development of artistic expression is a factor in the development of motor skills of children. The methodology used was Qualitative and Quantitative character as detailed descriptions of situations, events, people and observable behaviors occurred. As the techniques used was the psychology survey and direct observation within the driving Instruments Scale Oseretzki in order to measure the level of psychomotor development of children's center was applied investigated. The study concludes with a series of conclusions and recommendations for teacher performance in this area.